(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objective: To understand the perceptions and self-care needs of patients regarding intestinal stoma in the preoperative period. Method: Qualitative exploratory research performed in a surgical unit of a hospital in southern Brazil, with seven patients in the preoperative period of intestinal surgery. The data were collected through semi-structured interviews and submitted to thematic analysis of content. From the data analysis three thematic categories emerged: therapeutic itinerary and associated feelings; knowledge, perceptions and expectations regarding intestinal ostomy; and self-care needs of the patient with intestinal stoma. Results: The participants showed a lack of knowledge about intestinal stoma and evaluated this possibility as something negative, which would bring changes in lifestyle habits, with little information about care. Conclusion: It is evident the need to provide preoperative orientation for better acceptance and strengthening of the patient’s self-care in the postoperative period, appointing the nurse as an essential professional in this process.